2004
DOI: 10.1002/ts.123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed priming on growth and phenology of wheat under late‐sown conditions

Abstract: Seeds of four wheat varieties, Sonak, UP 2338, Raj 3765 and PBW 343, were treated with salts, water or growth regulator before sowing in the field in late winter. Sowing sprouted seeds resulted in more tillers, higher dry matter in leaves, stem and reproductive parts, and better grain yield. Priming with solutions of indole‐3‐acetic acid, KCl, water, ZnSO4 and Na2SO4 also gave more plant dry matter and grain yield than unprimed seeds. The plants from primed seeds took less time than the control to reach tiller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 1 publication
1
29
0
Order By: Relevance
“…Researchers observed that early plant establishment in late-sown wheat favors crops to complete tillering in time, which results in more productive tillers, more grains per spike, higher grain weight, and eventually a higher grain yield (Kant et al 2006;Farooq et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Researchers observed that early plant establishment in late-sown wheat favors crops to complete tillering in time, which results in more productive tillers, more grains per spike, higher grain weight, and eventually a higher grain yield (Kant et al 2006;Farooq et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Seed priming improves the germination rate, speed and uniformity even under less than optimum field conditions (Lee et al. 1998, Kant et al. 2006) thus enabling the establishment of uniform and good crop stand establishment.…”
Section: Discussionmentioning
confidence: 99%
“…2005, Farooq et al. 2006a,b), primed seeds are better able to complete the process of germination in a short time and cope with environmental stresses including low temperature (Kant et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficacy to seed priming techniques to advance the seedling germination rate, speed and uniformity of emergence even under less than normal field situation is well established (Lee et al, 1998;Kant et al, 2006;Farooq et al, 2008). During seed priming process, seeds are soaked in distilled water or solutions of low water potential, which allows pre-germination metabolic activities without actual germination, and seeds are then put out from the solution, rinsed and dried close to original weight to sanction routine handling (Bradford, 1986).…”
Section: Introductionmentioning
confidence: 99%